Uji Kelayakan Video Tutorial Pembuatan Pola Bunka Kelas X Mata Pelajaran Pembuatan Pola Di Sekolah Menengah Kejuruan : Pengembangan Media Pembelajaran, Pola Bunka - Enggar Kartikasari; naimatun sholikhah (Universitas Sarjanawiyata Tamansiswa, 2023)
The purpose of this study is to determine the feasibility level of learning media. This research method uses research and development (R&D) with the Four-D Models model which consists of 4 (four) stages, namely the define, design, develop, and disseminate stages. The validators in this study were media experts, material experts, and class X students as subjects. The object of this research is the development of the basic pattern making media for class X dressmaking bunka system. The instrument used for research is a questionnaire. Data analysis techniques using quantitative descriptive analysis. Based on the results of the research, it produced learning media for making the basic pattern of the bunka system body, and the feasibility level of the learning media for making the basic pattern of the bunka system body, which is very feasible. The results of the media expert's assessment obtained a percentage score of 87.36% in the very decent category. The results of the assessment by material experts obtained a percentage of 85.52% in the very feasible category. The results of student trials on a small scale obtained a percentage of 76.35% included in the very feasible category and the results of large-scale trials obtained a percentage of 85.23% in the very feasible category. The conclusion from the study is that the feasibility test of learning media for making the basic pattern of the bunka system based on video tutorials is very feasible to use as a learning medium at SMK Negeri 4 Yogyakarta. The purpose of this study is to determine the feasibility level of learning media. This research method uses research and development (R&D) with the Four-D Models model which consists of 4 (four) stages, namely the define, design, develop, and disseminate stages. The validators in this study were media experts, material experts, and class X students as subjects. The object of this research is the development of the basic pattern making media for class X dressmaking bunka system. The instrument used for research is a questionnaire. Data analysis techniques using quantitative descriptive analysis. Based on the results of the research, it produced learning media for making the basic pattern of the bunka system body, and the feasibility level of the learning media for making the basic pattern of the bunka system body, which is very feasible. The results of the media expert's assessment obtained a percentage score of 87.36% in the very decent category. The results of the assessment by material experts obtained a percentage of 85.52% in the very feasible category. The results of student trials on a small scale obtained a percentage of 76.35% included in the very feasible category and the results of large-scale trials obtained a percentage of 85.23% in the very feasible category. The conclusion from the study is that the feasibility test of learning media for making the basic pattern of the bunka system based on video tutorials is very feasible to use as a learning medium at SMK Negeri 4 Yogyakarta.